Identifying Rare FHB-Resistant Segregants in Intransigent Backcross and F2 Winter Wheat Populations - Clark, Anthony J.; Sarti-Dvorjak, Daniela; Brown-Guedira, Gina; Dong, Yanhong; Baik, Byung-Kee; Van Sanford, David A. (Frontiers in Microbiology, 2016)
Fusarium head blight (FHB), caused mainly by Fusarium graminearum Schwabe [telomorph: Gibberella zeae Schwein.(Petch)] in the US, is one of the most destructive diseases of wheat (Triticum aestivum L. and T. durum L.). Infected grain is usually contaminated with deoxynivalenol (DON), a serious mycotoxin. The challenge in FHB resistance breeding is combining resistance with superior agronomic and quality characteristics. Exotic QTL are widely used to improve FHB resistance. Success depends on the genetic background into which the QTL are introgressed, whether through backcrossing or forward crossing; QTL expression is impossible to predict. In this study four high-yielding soft red winter wheat breeding lines with little or no scab resistance were each crossed to a donor parent (VA01W-476) with resistance alleles at two QTL: Fhb1 (chromosome 3BS) and QFhs.nau-2DL (chromosome 2DL) to generate backcross and F2 progeny. F2 individuals were genotyped and assigned to 4 groups according to presence/ absence of resistance alleles at one or both QTL. The effectiveness of these QTL in reducing FHB rating, incidence, index, severity, Fusarium-damaged kernels (FDK) and DON, in F2-derived lines was assessed over two years. Fhb1 showed an average reduction in DON of 17.5%, and conferred significant resistance in 3 of 4 populations. QFhs.nau-2DL reduced DON 6.7 % on average and conferred significant resistance in 2 of 4 populations. The combination of Fhb1 and QFhs.nau-2DL resistance reduced DON 25.5% across all populations. Double resistant lines had significantly reduced DON compared to double susceptible lines in 3 populations. Backcross derived progeny were planted in replicated yield trials (2011 and 2012) and in a scab nursery in 2012. Several top yielding lines performed well in the scab nursery, with acceptable DON concentrations, even though the average effect of either QTL in this population was not significant. Population selection is often viewed as an “all or nothing” process: if the average resistance level is insufficient, the population is discarded. These results indicate that it may be possible to find rare segregants which combine scab resistance, superior agronomic performance and acceptable quality even in populations in which the average effect of the QTL is muted or negligible.